Weed Fermentation in Islamic Agriculture: Improving Forage Production in Smallholder Farming - Insani, A N; Mariam, M; Furqan, F (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2025)
This study aimed to identify potential weed species suitable as raw materials for fermentation technology in producing nutrient-rich organic fertilizers, thereby linking sustainable agricultural innovation with Islamic environmental ethics. A Completely Randomized Design (CRD) was employed with four treatments based on the volume of fermented weed-based fertilizer (0, 30, 40, and 50 mL) and three replications, resulting in a total of 36 experimental units. Observed parameters included plant height, leaf area, and chlorophyll content, while forage quality was analyzed through neutral detergent fiber (NDF), acid detergent fiber (ADF), and acid detergent lignin (ADL) composition. Results showed that weed fermentation had no significant effect on plant growth (P > 0.05) but significantly improved forage quality (P < 0.01) across fertilizer doses. Fermented weed-based fertilizer thus proved effective for enhancing the nutrient quality of green fodder sustainably. This research introduces a novel integration of weed fermentation technology and Islamic ethical principles, providing an innovative model for eco-friendly and faith-aligned agricultural practices. Keywords: Weed fermentation; organic fertilizer; forage quality; sustainable agriculture; Islamic agricultural ethics